SPESIASI Cr(III) DAN Cr(VI) PADA LIMBAH CAIR INDUSTRI ELEKTROPLATING - Dian Windy Dwiasi; Dwi Kartika (Universitas Jenderal Soedirman, 2008)
Speciation of Cr(III) and Cr(VI) in wastewater have been widely investigated. The species of Cr(III) and Cr(VI) in wastewater samples were determined by UV – Vis Spectrometry and Atomic Absorption Spectrometry (AAS). The method described is based upon the spectrophotometric determination of the magenta chromagen (λmax = 545 nm) formed when 1,5-diphenylcarbazide reacts with hexavalent chromium in sulphuric acid solution. Hexavalent chromium are determined by a calibration curve technique. The result showed that Cr(VI) concentration are still on the government regulation (Menteri Negara Kependudukan dan Lingkungan Hidup No. 03/MENKLH/II/1991).